مشكلات تعليم البلاغة باستخدام كتاب "شرح عقود الجمان في علم المعاني والبيان" في مدرسة قدسية الثانوية الإسلامية بقدس - Achmad Zuhri (LISANIA: Journal of Arabic Education and Literature, 2018)
This study aims to determine the learning process by using the book entitled uqudul Juman fi Al-ilmi almaani wal  Bayan and to know the learning problems by using the book in Qudsiyyah Islamic High School, along with solutions. This is a qualitative study by using observation, interviews, questionnaires methods, and documentation as the technique of collecting data. The results of this study show that the process of learning by using the book Syarh uqudul Juman Fi ilmu almaani wal bayan in Qudsiyyah Islamic High School Kudus is using the deductive method, while learning problems include the problems caused by internal factors which consist of learning materials, teacher, student, methods and time allocation. While the problems caused by external factors consist of the role of stakeholders, funding sources of school development and government policy.